Revolution and the Social Construction of Power. A Regressive History of Two Towns in Central Mexico, 2009–1910 (Tempo e Argumento, 2026)
This paper proposes to compare the social construction of power in two towns of the same municipality, located in the southwest of the State of Tlaxcala, in central Mexico. Despite their proximity, both towns had a very different history and a social hierarchy built on different bases. While San Miguel del Milagro was a sanctuary heir to the pre-Hispanic religious center of Cacaxtla, almost devoid of land when the Revolution broke out in 1910, Santa Apolonia Teacalco was a newly created town (former barrio of the cabecera) with land purchased from nearby haciendas and ranches. Through a regressive history used to compensate for the lack of access to ecclesiastical archival sources and the analysis of documents related to agrarian reform and civil justice lawsuits, we study the strategies of the families of these towns to build their power within their respective towns by occupying civil and religious positions and seeking to control political institutions. The main hypothesis is that, despite sharing a history closely linked to the church and having gone through the Revolution together, in a Zapatista zone and under the authority of the same authorities - municipal, judicial, state - the differentiated social structuring of each village was the determining element in the construction of their long-term bargaining power.
Keywords: Contemporary history; Mexican Revolution; Agrarian reform; Microhistory; Social structure